Host cell responses to Candida albicans biofilm-derived extracellular vesicles - Kulig, Kamila; Wronowska, Ewelina; Juszczak, Magdalena; Zawrotniak, Marcin; Karkowska-Kuleta, Justyna; Rapala-Kozik, Maria (Frontiers in Cellular and Infection Microbiology, 2025)
Candida albicans is a prevalent fungal pathogen responsible for infections in humans. As described recently, nanometer-sized extracellular vesicles (EVs) produced by C. albicans play a crucial role in the pathogenesis of infection by facilitating host inflammatory responses and intercellular communication. This study investigates the functional properties of EVs released by biofilms formed by two C. albicans strains—3147 (ATCC 10231) and SC5314—in eliciting host responses. We demonstrate the capability of C. albicans EVs to trigger reactions in human epithelial and immune cells. The involvement of EVs in pathogenesis was evidenced from the initial stages of infection, specifically in adherence to epithelial cells. We further established the capacity of these EVs to induce cytokine production in the epithelial A549 cell line, THP-1 macrophage-like cells, and blood-derived monocytes differentiated into macrophages. Internalization of EVs by THP-1 macrophage-like cells was confirmed, identifying macropinocytosis and phagocytosis as the most probable mechanisms, as demonstrated using various inhibitors that target potential vesicle uptake pathways in human cells. Additionally, C. albicans EVs and their cargo were identified as chemoattractants for blood-derived neutrophils. After verification of the in vivo effect of biofilm-derived EVs on the host, using Galleria mellonella larvae as an alternative model, it was demonstrated that vesicles from C. albicans SC5314 increased mortality in the injected larvae. In conclusion, for both types of EVs a predominantly pro-inflammatory effect on host was observed, highlighting their significant role in the inflammatory response during C. albicans infection.